Trust and Customer Engagement With E-Commerce Sellers Through The Role of Shopee Live Streaming - Arya Alifa, Muhamad Iqbal Fauzia; Roostika, Raden Roro Ratna (MEC-J (Management and Economics Journal), 2024)
With videos being broadcast in real time, live streaming services are increasingly popular in Indonesia, and many merchants have used them as a way to increase their sales. This study proposes a complete framework to examine the relationship between customer perceived value of live streaming, customer trust, and engagement based on literature in retail, adoption behavior, and e-commerce. The research method uses a quantitative approach with a survey method that results in 200 samples that have been distributed in Indonesia. This research was analyzed using PLS-SEM. The results showed that customer trust related to utilitarian value has a positive effect on live streaming. However, on hedonic values, the role of live streaming on customer trust only affects product trust, not their trust in the seller. The results of research related to customer engagement found that the role of live streaming can create utilitarian value and hedonic value, thus impacting customer trust and generating customer engagement in the process. However, this customer engagement only has a significant impact on customer trust in the seller, not with customer trust in the product. Implications of the results of this study. The implication results of this study provide insight into how e-commerce sellers can implement live streaming technology that attracts and retains customers. In addition to the function of live streaming, sellers should carefully design the atmosphere so that customers feel the utilitarian and hedonic values of shopping through live streaming, and in turn can affect customer demand.